The secret garden - Burnett, Frances Hodgson (New York Franklin Watts, 2007)
Ten-year-old orphan Mary Lennox comes to live in a lonely house on the Yorkshire moors and discovers an invalid cousin and the mysteries of a locked garden
Includes student guide
Hurg
5 8
Keywords: Friendship -- Fiction; Gardens -- Fiction; Orphans -- Fiction